Experimental characterization of two-particle entanglement through position and momentum correlations - Bergschneider, Andrea; Klinkhamer, Vincent M.; Becher, Jan Hendrik Willibald; Klemt, Ralf; Palm, Lukas; Zürn, Gerhard; Jochim, Selim; Preiss, Philipp (Nature physics, 2019)
Single-particle resolved measurements in an ultracold-atom experiment reveal an intuitive picture of quantum correlations, providing strong constraints on the full density matrix of the two-particle system in the presence of interactions.
Gesehen am 06.08.2019